The Effect of the Support and Assistance Groups Strategy on the Achievement of First-Year Intermediate School Female Students in the Arabic Grammar Subject - Ni'ma, Zainab Jumaa Fakhir; AL – Fayad, Tamathr Hameed Mahdee (Journal of Ecohumanism, 2024)
This research aims to determine the effect of the support and assistance group strategy on the achievement of first-year intermediate school female students in the Arabic grammar subject. The researcher randomly selected Al-Ibtihal Intermediate School for Girls, affiliated with the General Directorate of Education in Baghdad / Al-Rusafa III. The research sample consisted of (63) students; The experimental group, whose students will study Arabic grammar subject according to the strategy of support groups, consists of (32) female students, and Section (C) represents the control group with (31) female students. The researcher considered among the students of the two research groups some variables as: chronological age, intelligence test, linguistic ability test, and the academic achievement of parents. As for the research tool, the researcher prepared a test that measures achievement, consisting of (40) items, of the multiple-choice questions, distributed across three different questions papers. The researcher verified the validity and reliability of the test, extracted the discriminatory powers, and the difficulty coefficients of its items. Then the test was administered to the research sample students, and postponed for the students of the experimental group. The researcher studied the two research groups during the experimental period, which lasted for a full academic semester, in the academic year (2023-2024). The researcher statistically processes the data, used the t-test for two independent samples, the Chi-square test, the Pearson correlation coefficient, the difficulty coefficient equation, the distinctiveness coefficient equation, and the Spearman- Brown equation. After analyzing the data, the research concluded that there is a statistically significant difference between the average grades of the students of the two research groups in the Arabic grammar achievement skills, in favor of the experimental group at a significance level of (0.05).